Development syariah compliant application of e nursing kids - Siti Fatimah, Salleh; Dhamirah Nursakinah, Mohamad Safir; Halimatus Saadiah, Mohamad Safir (2020)
The e - AS app (e-AS) is a mobile and user-friendly smartphone application, aimed at documenting the information of children, parents, siblings and nursing siblings as a result of fetal factors. eAS is able to provide early childhood exposure and education to young people, as well as exposure to the importance and need of documentation for nursing children. The methodology used in developing the eNursing Kids application is to use the modified Waterfall Model to be more organized and managed. The results of this study found that documenting breastfeeding online was very significant in addressing the problems of breastfeeding because of the occurrence in breastfeeding. This application is a system that capable of storing user-registered information and also operates to print birth certificates to be certified by the district registrar at the State Religious Office. The e-AS application will be introduced to the state Islamic religious office for official implementation purposes